Permittivity Characterization of Ferroelectric Thin-Film Hafnium Zirconium Oxide Varactors up to 170 GHz - Abdulazhanov, S.; Le, Q. H.; Huynh, D. K.; Lehninger, D.; Kampfe, T.; Gerlach, G. (Conference digest / Device Research Conference, 2023)
Ferroelectric materials are commonly utilized in mmWave applications as tunable devices. They offer low-loss operation at frequencies above 20 GHz due to their high dielectric permittivity, surpassing conventional semiconductor materials. Perovskite-based ferroelectrics, such as barium strontium titanate (BST) and lead zirconium titanate (PZT), are the most extensively used ferroelectrics to date due to their superior tuning properties and low dielectric losses. Recently, hafnium oxide (Hf02) has become the subject of significant interest after its ferroelectricity was discovered [1]. When doped with zirconium, resulting Hf x Zr 1-x O 2 (HZO) crystallizes into orthorhombic ferroelectric phase at lower temperatures [2], thereby fitting perfectly into the thermal budget of conventional Back-End-of-Line (BEoL) process. This gives it advantages over conventional ferroelectrics and thus makes it a promising candidate for use as a ferroelectric varactor for tuning RF circuits. Previously, HZO varactor was analyzed in our group at mmWave frequencies up to 110 GHz [3]. In this paper, we provide a more extended mmWave analysis ranging from 110 GHz to 170 GHz, which represents the highest frequency range reported for this material.